Autorzy:Wojciech Babiański, Lech Chańko, Joanna Czarnowska, Grzegorz Janocha
Wydawnictwo:Nowa Era
Rok wydania:2016
Uzasadnij, że poniższa równość jest prawdziwa 4.38 gwiazdek na podstawie 8 opinii

Uzasadnij, że poniższa równość jest prawdziwa

2Zadanie
3Zadanie
4Zadanie
5Zadanie
6Zadanie
7Zadanie
1Zadanie
2Zadanie

`a)` 

`L=x^2+y^2` 

`P=(x+y)^2-2xy=x^2+2xy+y^2-2xy=x^2+y^2` 

`L=P` 

 

 

`b)` 

`L=x^2+y^2` 

`P=(x-y)^2+2xy=x^2-2xy+y^2+2xy=x^2+y^2` 

`L=P` 

 

 

`c)` 

`L=(x+y)^2+(x-y)^2=x^2+2xy+y^2+x^2-2xy+y^2=2x^2+2y^2=2(x^2+y^2)` 

`P=2(x^2+y^2)` 

`L=P` 

 

`d)` 

`L=(x+y)^2-(x-y)^2=x^2+2xy+y^2-(x^2-2xy+y^2)=x^2+2xy+y^2-x^2+2xy-y^2=4xy` 

`P=4xy` 

`L=P`